Influence of advanced maternal age and gestational age on the morphology of human placenta - Jovičić Sanja; Ljubojević Vesna; Barudžija Maja; Amidžić Ljiljana; Škrbić Ranko; Nikolić Ivan R. (Scripta Medica)
Background/Aim: The placenta is an extraembryonic organ necessary for foetal development. Due to its availability and high content of stem cells and growth factors, placenta tissue has found its application in regenerative medicine. The aim of this paper was to determine whether the age of the pregnant woman or the gestational age affects the morphology of the term placenta and whether placentas of advanced maternal age are suitable for application in regenerative medicine. Methods: In this research 30 placentas of healthy pregnant women, aged from 18 to 42 years and from 36 up to 41 weeks of gestational age were used for analyses. Tissue samples were stained with standard haematoxylin and eosin staining and immunohistochemical staining with anti-CD34 antibody. The parameters of volume density of chorionic villi, intervillous spaces and fibrinoids, as well as the thickness of the placental barrier were determined. Results: The volume densities of chorionic villi and fibrinoids were higher in placentas of advanced maternal age, as well as in placentas of gestational age from 38 to 41 weeks of gestation, while the volume of intervillous spaces was lower in these groups. With increased maternal and gestation age, the placental membrane thickens. Conclusion: When sampling placentas for regenerative medicine purposes, only the placentas from pregnant women younger than 35 years of age and whose gestational age are not exceeding 38 weeks should be selected.